Admissible consensus of uncertain fractional-order singular multiagent systems with actuator fault. (February 2021) - Zhang, Xuefeng; Dong, Jia
Consensus of fractional-order singular multiagent systems is considered in this article. The model of uncertain systems with actuator fault is established, and its admissible consensus in the field of fractional-order systems is studied. First, the uncertain singular multiagent systems with actuator fault are proposed. Then, a state feedback controller and a state consensus protocol with an observer based on output information are designed. Then, new consensus criteria of uncertain fractional-order singular multiagent systems are proposed. Finally, for the sake of demonstrating the validity of proposed results, some relevant numerical examples are provided.